Stable potassium isotopes (41K/39K) track transcellular and paracellular potassium transport in biological systems - Higgins, John A.; Ramos, Danielle Santiago; Gili, Stefania; Spetea, Cornelia; Kanoski, Scott; Ha, Darren; McDonough, Alicia A.; Youn, Jang H. (Frontiers in Physiology, 2022)
As the most abundant cation in archaeal, bacterial, and eukaryotic cells, potassium (K+) is an essential element for life. While much is known about the machinery of transcellular and paracellular K transport – channels, pumps, co-transporters, and tight-junction proteins - many quantitative aspects of K homeostasis in biological systems remain poorly constrained. Here we present measurements of the stable isotope ratios of potassium (41K/39K) in three biological systems (algae, fish, and mammals). When considered in the context of our current understanding of plausible mechanisms of K isotope fractionation and K+ transport in these biological systems, our results provide evidence that the fractionation of K isotopes depends on transport pathway and transmembrane transport machinery. Specifically, we find that passive transport of K+ down its electrochemical potential through channels and pores in tight-junctions at favors 39K, a result which we attribute to a kinetic isotope effect associated with dehydration and/or size selectivity at the channel/pore entrance. In contrast, we find that transport of K+ against its electrochemical gradient via pumps and co-transporters is associated with less/no isotopic fractionation, a result that we attribute to small equilibrium isotope effects that are expressed in pumps/co-transporters due to their slower turnover rate and the relatively long residence time of K+ in the ion pocket. These results indicate that stable K isotopes may be able to provide quantitative constraints on transporter-specific K+ fluxes (e.g. the fraction of K efflux from a tissue by channels vs. co-transporters) and how these fluxes change in different physiological states. In addition, precise determination of K isotope effects associated with K+ transport via channels, pumps, and co-transporters may provide unique constraints on the mechanisms of K transport that could be tested with steered molecular dynamic simulations.